Aesthetic Judgement and Political Judgement - Nielsen, Henrik Kaare (The Nordic Journal of Aesthetics, 2012)
Prominent positions in the contemporary theoretical field of the humanities tend to conceptualize late modern communities in general as aesthetic communities of taste. In regard to political communities, this means reducing the political to an implication of the aesthetic discourse. This article argues for addressing the aesthetic and the political as distinct discourses that are, on the other hand, always engaged with each other in a conflictual interplay. Both discourses draw on and appeal to the ability of judgement, but according to their own distinct principles, and depending on their respective weight in the conflictual interplay, this entails quite different perspectives with regards to political practice and community formation.